CALCULATION IN ECONOMETRIC MODELS OF HUMAN CAPITAL FINANCING IN INNOVATION MANAGEMENT IN UZBEKISTAN - Bakhtiyar, Kalmuratov; Berdakh, Izzetov; Jamila, Yusupova; Alima, Shamuratova («YANGI O’ZBEKISTON IQTISODIYOTI», 2026)
This paper provides a comprehensive analysis of the about how to create an innovative enterprise and create an innovative organization that will contribute to the development of the organizational and economic mechanism and the modernization of econometric models. The study utilizes a mixed-methods approach, combining statistical analysis of key economic indicators with qualitative insights from expert interviews